Diversity insect in the Vegetative Phase of Arenga pinnata (wurmb) merr. in Tanjung Miring Village, Muara Enim - Riko Firmanto; Weri Herlin; Yulia Pujiastuti (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2025)
One of the factors that support the growth of sugar palm plants was the presence of insects that indirectly play an important role in the ecosystem of these plants. The study aimed to determine the abundance, diversity, and role of insects associated with young sugar palm plants (vegetative) in Tanjung Miring Village. The method used was purposive random sampling by setting yellow sticky traps and pitfall traps. Data collection techniques were obtained through direct observation in the field by setting two traps and interviews with sugar palm plant farmers using a questionnaire. The results showed that there were 21 insect species belonging to 18 families from 8 orders. Three important insect groups consisted of 9 types of pollinating insects, 7 types of herbivorous insects, and 5 types of decomposing insects. The abundance of pollinating and decomposing insects was dominated by the orders Hymenoptera and Diptera with a total of 338 individuals. The highest insect species diversity was found in the yellow trap with 13 species and a Shannon-Wiener diversity index (H') of 2.17. While pitfall traps, only 8 species of insects were found with an H' value of 1.43. The high diversity and abundance of yellow traps showed the dominance of active flying insects, especially pollinators, with the highest relative abundance (Di=2.43). The complex ecosystem of the sugar palm groves is an important habitat for various insects with complementary ecosystem functions.